Building academic relations and solidarity through humour at work - Nor Azikin Mohd Omar; Jariah Mohd Jan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The use of humor at the workplace has been well researched in Western countries but such studies in Asian societies are still in its infancy. This study aims to investigate the utilization of humour in academic meetings. In particular, it aims to investigate the factors that influence rapport building through humour in asymmetrical and symmetrical relationships. Data for the study comprise of video recordings of naturally occurring interaction between academic staff meeting. Hay’s Taxonomy of Functions of Humour (1995) was used to categorise the functions of humour that mainly maintains solidarity among academicians. Results indicate that friendly teasing and “all-together-now” i.e. AATN (Coates 1989) are frequently used amongst academics to develop and maintain solidarity. Humour appreciation is also shown to strengthen, construct and maintain collegiality in the workplace setting.